Предмет: Алгебра, автор: AzeThomas

Пожалуйста помогите!!!!

Приложения:

Ответы

Автор ответа: zveryakovanata
0

Ответ:

Объяснение: y=x/(x²-4) ⇒

dy/dx= y'(x) = (1·(x²-4)- x·2x) / (x²-4)²= (x²-4 -2x²) / (x²-4)²= -(x²+4)/(x²-4)²

d²y/dx² = y"(x)=((-2x)·(x²-4)² +(x²+4)·2·(x²-4)·2x) / (x² - 4)⁴ =  

=(-2x·(x⁴-8x²+16)+4x(x⁴-16)) /(x²-4)⁴= (-2x⁵+16x³-32x+4x⁵-64x) /(x²-4)⁴=

(2x⁵+16x³-96x) /(x²-4)⁴=2x(x⁴+8x²-48) /(x²-4)⁴ =

=2x(x²-4)(x²+12) /(x²-4)⁴ = 2x(x²+12) /(x²-4)³

Похожие вопросы
Предмет: Окружающий мир, автор: юл12я234